A Techno-Economic Comparative Study of a Grid-Connected Residential Rooftop PV Panel: The Case Study of Nahr El-Bared, Lebanon - Camur, H.; Kassem, Y.; Alessi, E. (Engineering, Technology & Applied Science Research, 2021)
Lebanon suffers from daily electricity shortages. The country has paid much attention to renewable energy sources, particularly solar, to gradually replace conventional energy. Installing a photovoltaic (PV) system becomes increasingly attractive for residential consumers due to the rising electricity tariff rates while it reduces the dependency on domestic power generators. No known study has dealt with the investigation of potential grid-connected rooftop PV systems with various sun-tracking modes and PV technologies in Nahr El-Bared, Lebanon. Consequently, the main objective of the current paper is to investigate the feasibility of a 5kW grid-connected PV system of various technologies (mono-crystalline silicon and poly-crystalline silicon) and sun-tracking modes including fixed tilt and 2-axis systems for rooftop households in Lebanon. The Nahr El-Bared camp was the case study was of the paper. RETScreen Expert software was used to evaluate the techno-economic performance of the proposed systems. The results show that the annual electrical energy from a fixed 5kW PV panel tilted at an optimal angle ranged from 8564.47kWh to 8776.81kWh, while the annual electrical energy from the PV tracking system was within the range of 11511.67-12100.92kWh. This amount of energy output would contribute significantly to reduce the energy shortage in the country. A typical household was selected to establish a load profile and load supply during both grid availability and outage periods. The highest energy consumption that can be covered by the PV systems was recorded during the spring and summer seasons. Also, the average energy production cost ranged from 0.0239 to 0.0243$/kWh for all the proposed systems. It was concluded that a 5kW grid-connected rooftop PV system could be economically justifiable. Finally, this study tried to increase the awareness about utilizing PV sun-tracking systems and the feasibility of small-scale grid-connected rooftop PV systems in the selected regions. The results of this research can help investors in the energy and building sectors.